Risk factors for choledocholithiasis: a literature review - Martínez, Glendy Alejandra (International Journal Of Community Medicine And Public Health, 2023)
Choledocholithiasis is a disease characterized by the presence of stones in the common bile duct, which can lead to serious complications. This literature review aims to explore in detail the risk factors associated with choledocholithiasis, examining its epidemiology, clinical significance and aspects related to its diagnosis, surgical treatment and complications. An exhaustive search of the updated scientific literature was carried out, consulting various specialized databases, in order to provide a complete and updated vision on this relevant topic in the medical field.